Extracellular Vesicle-Associated miRNAs as a Biomarker for Lung Cancer in Liquid Biopsy - He, Xue; Park, Sujeong; Chen, Yan; Lee, Heedoo (Frontiers in Molecular Biosciences, 2021)
Extracellular vesicles (EVs) are cell-derived membranous vesicles that are secreted into biofluids. Emerging evidence suggests that EVs play an essential role in the pathogenesis of many diseases by transferring proteins, genetic material, and small signaling molecules between cells. Among these molecules, microRNAs (miRNAs), a type of small noncoding RNA, are one of the most important signals and are involved in various biological processes. Lung cancer is one of the leading causes of cancer-related deaths worldwide. Early diagnosis of lung cancer may help to reduce mortality and increase the 5-year survival rate and thereby reduce the associated socioeconomic burden. In the past, EV-miRNAs have been recognized as biomarkers of several cancers to assist in diagnosis or prognosis. In this review, we discuss recent findings and clinical practice for EV-miRNAs of lung cancer in several biofluids, including blood, bronchoalveolar lavage fluid (BALF), and pleural lavage.